PENGARUH KOMITMEN TERHADAP KIINERJA PEGWAI DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING PADA KANTOR KECAMATAN SIANTAR KABUPATEN SIMALUNGUN - Bagus Habi Wahyu; Darwin Lie; Efendi Efendi; Sudung Simatupang (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2019)
Research results can be summed up as follows: 1. The quality of Commitmen of Employee is quite good, Work Discipline is good , and Employee Performance was quite satisfied. 2. There is a positive influence between commitmen toward against work disciplin. There is a positive influence between Work Discipline against Employee Performance. 3. There is moderately high and positive correlation between Commitmen of Employee against a Work Discipline. means there is a high and positive correlation between Work Discipline with employee performance. 4. The results of the hypothesis H0 is rejected, meaning that Commitmen of employee have a positive and significant impact on Employee performance through Work Discipline as Intervening Variables. Keywords: Compensation, Facilities, and Job Satisfaction